Regularisation and the Mullineux Map - Fayers, Matthew (The Electronic Journal of Combinatorics, 2008)
We classify the pairs of conjugate partitions whose regularisations are images of each other under the Mullineux map. This classification proves a conjecture of Lyle, answering a question of Bessenrodt, Olsson and Xu.